Reframing Sustainable Tourism / Stephen F. McCool, Keith Bosak Editors - Bosak, Keith Editors
This book examines the need for a new way of describing sustainable tourism and also looks at the frameworks needed to rethink how to apply this to communities, private operators and protected area managers. It makes it clear that tourism is just one of many human activities that affects host communities. The work includes informative and provocative case studies with realistic applications. References included in the book will help graduate students formulate new hypotheses and suggest literature for them. Tools and techniques useful to tourism practitioners suggest innovative approaches to marketing, management and community development